Trabecular bone texture detected by plain radiography and variance orientation transform method is different between knees with and without cartilage defects - Wolski, Marcin; Stachowiak, Gwidon; Dempsey, A; Mills, P; Cicuttini, F; Wang, Y; Stoffel, K; Lloyd, D; Podsiadlo, Pawel (John Wiley & Sons, Inc., 2011)
The objective of this work is to evaluate differences in trabecular bone (TB) texture between subjects with and without tibiofemoral cartilage defects using a variance orientation transform (VOT) method. A case–control study was performed in subjects without radiographic knee osteoarthritis (OA) (K&L grade <2) matched on sex, BMI, age, knee compartment, and meniscectomy where cases (n = 28) had cartilage defects (grade ≥2) and controls (n = 28) had no cartilage defects (grade <2). Cartilage defects were assessed from MRI using validated methods. The VOT was applied to TB regions selected on medial and lateral compartments in knee X-rays and fractal signatures (FS) in the horizontal (FSH) and vertical (FSV) directions, and along the roughest part of TB (FSSta) and texture aspect ratio signatures (StrS), at different trabecular image sizes (0.30–0.70 mm) were calculated. Compared with controls, FSV for cases were higher (p < 0.011) at image sizes 0.30–0.40 mm and 0.45–0.55 mm in the medial compartment. In the lateral compartment, FSH and FSSta for cases were higher (p < 0.028) than those for controls at 0.30–0.40 mm and 0.45–0.55 mm, while FSV was higher (p < 0.02) at 0.30–0.40 mm. TB texture roughness was greater in subjects with cartilage defects than in subjects without, suggesting thinning and fenestration of TB occur early in OA and that the VOT identifies changes in TB in knees with early cartilage damage. No differences in StrS (p > 0.05) were found.